The assessment of HER2 status and its clinical implication in breast cancer. Issue 2 (February 2020) - Hou, Yanjun; Nitta, Hiroaki; Parwani, Anil V.; Li, Zaibo
Abstract: Amplification and overexpression of human epidermal growth factor receptor 2 (HER2) in breast cancer is associated with an adverse prognosis. The introduction of trastuzumab and lapatinib has substantially improved the clinical outcomes of patients with HER2-positive breast cancer. The key element of the successful application of anti-HER2 therapies in real-world has been the selection of candidates for treatment based on the level of HER2 positivity of the tumor. HER2 status of breast cancer is clinically assessed by HER2 protein expression with immunohistochemistry (IHC) or HER2 gene amplification with in situ hybridization (ISH). The 2018 American Society of Clinical Oncology and the College of American Pathologists (ASCO/CAP) HER2 guideline focused update revised the HER2 scoring criteria. Digital image analysis (DIA) has emerged as an objective and reproducible IHC scoring method and the ASCO/CAP HER2 guideline has acknowledged DIA as a diagnostic modality. In this article, we aim to review the assessment of HER2 status and its clinical application in breast cancer.